Correlation Between Structure And The Magnetic Properties Of Amorphous And Nanocrystalline Fe74Cu0.5Nb3Si13.5B9 Alloys (Journal of Bangladesh Academy of Sciences, 2012)
Structural and magnetic measurements have been performed on the FINEMET type of ribbons with nominal composition of Fe74Cu0.5Nb3Si13.5B9 synthesized by rapid solidification technique. The crystallization behavior and the nanocrystal formation have been studied by differential thermal analysis (DTA) and X-ray diffraction (XRD). The crystallization onset temperatures determined by XRD are in good agreement with DTA results. Magnetic permeability and magnetization measurements have been carried out using inductance analyzer and vibrating sample magnetometer (VSM). Magnetic permeability sensitively depends on the annealing temperature which increases sharply with the increase of annealing temperature. Maximum permeability corresponding to optimum annealing temperature (Ta) was observed at Ta = 575°C. Saturation magnetization, Ms, increases with Ta for the sample and finally decreases for annealing at a temperature much higher than peak crystallization temperature. The results show that the amounts of Cu and Nb are very important for the soft magnetic properties of FINEMET alloys. Key words: FINEMET; XRD; Grain size; Permeability; Saturation; Magnetization DOI: http://dx.doi.org/10.3329/jbas.v35i2.9423 JBAS 2011; 35(2): 187-195